VERB PHRASE IN ENGLISH AND MINANG LANGUAGE - Yenita Uswar (Universitas Potensi Utama, 2019)
This study details about verb phrase in English and Minang Language. The objective of this research is to find the similarities and differences of verb phrase in English and Minang Language by using tree diagrams structures in Syntax. The research analyze about the formation and function of verb phrase in both languages. The data to support this study were collected by reading references books and the Minang’s poem. The findings showed the similarities of verb phrase in English and Minang language based on forms and functions. The similarities of both languages could be formed by adding Verb + Noun, Verb + Adjective, Verb + Adverb, and Numeral Phrase. While, verb phrase in English could be formed by Prepositional Phrase.